Internet and Pornography Use During the COVID-19 Pandemic: Presumed Impact and What Can Be Done - Awan, Hashir Ali; Aamir, Alifiya; Diwan, Mufaddal Najmuddin; Ullah, Irfan; Pereira-Sanchez, Victor; Ramalho, Rodrigo; Orsolini, Laura; de Filippis, Renato; Ojeahere, Margaret Isioma; Ransing, Ramdas; Vadsaria, Aftab Karmali; Virani, Sanya (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic continues to cause an immense psychosocial strain worldwide. Excessive use of the internet during these psychologically trying times, fueled by physical isolation as a result of lockdowns, has translated into dysfunctional behaviors. A growing body of evidence suggests an unprecedented increase in internet use and consumption of online pornography during the pandemic, and possibly even directly caused by it. In this review, the authors report data from relevant sources to show the rise in pornography use during lockdowns in different countries worldwide. In addition to a brief overview of the neurobiology of internet addiction broadly and problematic online pornography use specifically, similarities with substance use disorders are explained. Further, the current status of the debate about defining diagnostic criteria is discussed. Finally, the review sheds light on the potential detrimental outcomes during the future post-pandemic “re-adaptation”, while simultaneously offering preventative and management strategies for harm reduction. The authors conclude that foresightedness with utilizing existing tools and therapies and exercising appropriate amounts of caution could go a long way in addressing the challenges that lie ahead in the post-pandemic era.